A survey on the performance and status of disseminated elite N’Dama cattle breeding bulls at the multiplier tier of an Open Nucleus Breeding Scheme in The Gambia for the period 2011 to 2019 - Secka, Arss; Camara, Lamin; Jeng, Momodou; Olaniyan, Olawale (Genetic Resources, 2022)
The objectives of this survey conducted in 2020 were to profile Multiplier farmers, assess the performance of disseminated N’ breeding bulls at the multiplier cattle herds, and inquire about cattle health and production challenges. Thirty-three farmers living in 33 villages in 5 regions of The Gambia who received 52 elite N’ breeding bulls from the West Africa Livestock Innovation Centre (WALIC) Nucleus tier were interviewed. The results showed that the disseminated bulls’ performance is generally satisfactorily as asserted by 28 respondents. Twenty-eight respondents reported that the bulls were healthier, 31 ascribed these bulls with stronger libido, 20 asserted that female offspring from these bulls produced more milk, and 26 claimed that offspring had a faster growth rate. A total of 473 calves have been sired by these bulls thus far. However, only 19 bulls are currently present at the multiplier herds due to the exit of 33 bulls arising from various causes. Cattle production challenges reported by farmers included decreasing grazing lands, rampant bush fires, and inadequate watering points; whilst listed health constraints included inadequate access to veterinary drugs and disease prevalence. The multiplication of the disseminated breeding bulls at the Multiplier tier has progressed well in terms of sired offspring, but further transfer to the Commercial Farmer tier is slow. This situation calls for more sensitization of farmers, increased visibility of the breeding programme, and utilization of other reproductive techniques such as artificial insemination to reach more cows for enhanced genetic improvement and productivity.